The Influence of Service Quality toward Customer Loyalty: A Case Study at Alfamart Abdurahman Saleh Bandung - Rizki Faiz Al-Haqam; Arif Yusuf Hamali (Binus Business Review, 2016)
The research objectives were to determine the correlation between service quality and customer loyalty, and also to analyze the influence of service quality on customer loyalty at Alfamart Abdurahman Saleh Bandung. Respondents of this research were 70 respondents with nonprobability sampling technique done by incidental sampling. The method used is descriptive and associative, which tested the connection using the Spearman rank correlation analysis, to test the hypothesis by t-test, and to determine the accuracy of measurement using the validity and reliability test. Results of the validity and reliability test of variables X and Y are valid and reliable. Calculations were performed using SPSS software ver. 19. The results of this research show that service quality is in the category of good and customer loyalty is also in the category of good. Results show that the correlation of service quality with customer loyalty at Alfamart Abdurahman Saleh Bandung is in the strong relation based on the interpretation of r value correlation coefficient. The hypothesis is proved that there is the influence of service quality on customer loyalty at Alfamart Abdurahman Saleh Bandung significantly.